2006
DOI: 10.1189/jlb.0906584
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CD8+ T cell repertoire in identical twins discordant and concordant for multiple sclerosis

Abstract: Autoreactive CD4+ and CD8+ T cells directed against CNS autoantigens may play a role in the development of multiple sclerosis (MS). Identical twins share the same genetic background but not the TCR repertoire that is shaped by the encounter with self or foreign antigens. To gain insights into the interplay between MS and T cell repertoire, peripheral blood CD4+ and CD8+ T lymphocytes and their CCR7+/CCR7- subsets from five pairs of identical twins (four discordant and one concordant for MS; none of which had t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 65 publications
(78 reference statements)
1
19
0
Order By: Relevance
“…MZ twins are therefore not genetically identical at these loci, which could explain the low concordance of MS and other immune mediated diseases among MZ twins [183]. In accordance with this hypothesis, CDR3 spectratyping of TCRs showed significantly different patterns between affected and the unaffected MZ twins [184,185]. Moreover, T cells from MZ twins concordant for MS used similar TCR V genes in response to both an autoantigen (MBP) and a foreign antigen (tetanus toxoid), whereas T cells from discordant MZ twins used different TCR V genes [186].…”
Section: Immune Receptor Genessupporting
confidence: 74%
“…MZ twins are therefore not genetically identical at these loci, which could explain the low concordance of MS and other immune mediated diseases among MZ twins [183]. In accordance with this hypothesis, CDR3 spectratyping of TCRs showed significantly different patterns between affected and the unaffected MZ twins [184,185]. Moreover, T cells from MZ twins concordant for MS used similar TCR V genes in response to both an autoantigen (MBP) and a foreign antigen (tetanus toxoid), whereas T cells from discordant MZ twins used different TCR V genes [186].…”
Section: Immune Receptor Genessupporting
confidence: 74%
“…These findings correlate with a previous study finding little or no difference in the clonal composition of myelin antigen-reactive T-cells between MS patients and healthy subjects (Hafler et al, 1996). Possibly a more detailed breakdown of the CD8+ T-cell population would provide more insights, such as one performed by Somma et al, where they found a skewed repertoire in 3 pairs of MS discordant twins when they divided the CD8+ T-cell fraction into CCR7 negative (effector memory) and CCR7 positive (central memory, naïve) fractions (Somma et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…One thing is clear, even in identical twins possessing the same genetic information, the T-cell repertoires are distinct and in some cases may account for discordance in the development of diseases such as type 1 diabetes or multiple sclerosis. [8][9][10] Standard quantitative assays for measuring specific CD8 ϩ T-cell responses, such as pMHCI-labeled tetramer, intracellular cytokine staining, and enzyme-linked immunospot (ELISPOT), have a limit of detection of 5 ϫ 10 Ϫ5 . Moreover, the latter 2 assays monitor functional activity and thus are not adequate for studying naive antigen-specific CD8 ϩ T cells.…”
Section: Introductionmentioning
confidence: 99%